A bibliography of quaternary entomology: (qbib) - Buckland, Philip I. (Umeå University, 2019)
Originally published in 1991 (Buckland & Coope, 1991), this is the most comprehensive bibliography of articles and books on Quaternary fossil insects available on the planet. It covers over 2100 works on their use in palaeoclimatology, palaeoecology, forensic archaeology, and environmental archaeology. Updates are periodically posted here, at www.bugscep.com, and on other open resources.

The dataset was originally published in DiVA and moved to SND in 2024.

Denna bibliografi publicerades ursprungligen 1991 (Buckland & Coope, 1991) och är den mest omfattande bibliografin över artiklar och böcker om fossila insekter från kvartärtiden som finns tillgänglig i världen. Den omfattar över 2100 verk om deras användning inom paleoklimatologi, paleoekologi, rättsarkeologi och miljöarkeologi. Uppdateringar läggs regelbundet ut här, på www.bugscep.com och på andra öppna resurser.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
A bibliography of quaternary entomology: (qbib)
Keywords: environmental archaeology; environmental archaeology; publications; publications; Fossil insects; Fossil insects; Quarternary Geology; Quarternary Geology; Entomology; Entomology; references; references; bibliography; bibliography; Quaternary science; Quaternary science; Geology; Geologi; Ecology; Ekologi; Biological Systematics; Biologisk systematik; History and Archaeology; Historia och arkeologi